Tanglewreck - Winterson, jeanette (London Blooms Bury, 2006)
A little way in the future, time is distorting. Time Tornadoes are causing havoc. People are whirled out of their own time, never to return and a woolly mammoth has been seen on the banks of the River Thames. But time is big business, and who ever gets control of time, controls life as we know it!
Keywords: Time travel -- Clocks and watches -- Space and time